CUBA IN THE EARLY YEARS AS A REPUBLIC. NOTES FROM THE CUBAN HISTORIOGRAPHY. (Tzintzun, Revista de Estudios Históricos, 2016)
The article analyzes the general tendencies of Cuban historiography referent to thedifferent discussions that the first Cuban presidential election provoked in thehistorical memory at the end of the twentieth century. We consider that there aretwo main elements that are involved in the explanation of the meaning and theimplications of the mentioned presidential election and the establishment of therepublic. In may 1902, from which the Cuban historiography dedicates the topic.One refers to the hegemonic condition, the expansionist impulse and the Americaninterest in the island. The other aspect focuses on the efforts of the social andCuban politicians’ factors to obtain the independence and take the first steps inbuilding their national identity. The historiography journey does not attempt togive an exhaustive bibliographic list, but in supplying a balance about the mainideological and political influences of the press notes carried out in Cuba aroundthe Republic coming.
Keywords: Cuba; First Republic; historiography; United States